Mejniki gospostva Jama (Luegg) v gozdovih Hrušice - Triglav Čekada, Mihaela (Geodetski vestnik, 2025)
In this paper, old cadastral municipalities boundary marks are presented that have been preserved in the forests of Hrušica above Postojna, Nanos, Javornik above Črni Vrh and Javorniki above Cerknica (Slovenija). The study area has been limited to the former estate of Jama (Predjama), for which a description of its boundary has been preserved from 1589. Over the centuries, its boundaries have been transformed into the boundaries of cadastral municipalities, administrative and forestry units. The boundary marks from 1691, 1823 and the period 1863–1881 were examined in the field. The inscriptions HL, HW, HH and BHA are carved on them. Depending on their location and time of erection, these are abbreviations for estates, administrative districts, or forestry units. In this article we describe 30 geodetic marks and two churches. The church of St. Lavrence above Studeno has a stone slab preserved on which the inscribed text explains that its church tower presented the border point of the estate Jama agreed upon in the year 1820. The church of St. Bric on Nanos has a stone with carved inscriptions preserved in the outer wall, which, according to folklore, was also the border stone of the same estate in the past.
Keywords: administrative units; cadastral municipality boundary marks; forest Hrušica above Postojna; forestry units; gozdarska razdelitev; gozdovi Hrušice nad Postojno; grad Jama (Predjama); mejniki katastrskih občin; Predjama (Luegg) Castle; upravna razdelitev; Windischgrätz